Invectivas latinescas. Anatomía de la " Expostulatio Spongiae " en defensa de Lope de Vega - Conde Parrado, Pedro (2012)
Estudio de la polémica planteada en 1617-1618 por la publicación de la Spongia de Pedro de Torres Rámila contra Lope de Vega y la anónima respuesta escrita en defensa de este y titulada Expostulatio Spongiae. Partiendo del análisis del peculiar latín empleado en ambas obras, se demuestra cómo una buena parte de la Expostulatio está compuesta a partir de, al menos, otras cinco obras latinas coetáneas. Ese descubrimiento permite plantear, así mismo, una hipótesis acerca del posible autor de dicha obra.
This is a study on the literary controversy prompted in 1617-1618 due to the publication of Pedro de Torres Rámila's Spongia against Lope de Vega and the anonymous Expostulatio Spongiae, written in order to support Lope. On analysing the particular use of the Latin language in both works, we can prove that a good deal of Expostulatio was made up assembling fragments of, at least, five contemporary Latin works. That discovery allows us to propose, as well, a hypothesis on a possible author of Expostulatio.
Keywords: Vega, Lope de, -- 1562-1635; Torres Rámila, Pedro de, -- 1583-1658; Literatura latina